Spatio–Temporal Variation of Chlorophyll, Nutrients and Productivity in Lagos Lagoon, Lagos Nigeria Using Remote Sensing Approach (2022)
Spatio–temporal variation in Chlorophyll, Nutrients and Primary Productivity of some selected sampling stations in Lagos lagoon were investigated using conventional method from November 2019 to July 2020, in order to compare the result with data from satellite image using MODIS Aqua. Global Positioning Receiver was used to capture the geographic coordinates of the sampling stations. Water sampling was carried out monthly using standard methods during wet and dry seasons. The observed data were subjected to statistical analysis using Microsoft Excel and SPSS. version 20. In wet season, the highest mean value for Chlorophyll a (1.15±0.02 μg/L) was recorded in Ofin while the lowest values (0.06±0.01 μg/L) was observed in Okobaba. During the dry season, the highest mean value (0.75±0.10 μg/L) was in Ofin while the lowest mean value (0.27±0.0.08 μg/L) was recorded in Ibeshe. The MODIS satellite variation in chlorophyll-a showed that the highest value of highest recorded value (1.37±0.00 μg/L) was in wet season (Ijede) while the lowest value (0.12±0.01 μg/L) was observed in dry season (Okobaba). The highest transparency value (0.97±0.01 mg/L) was recorded in dry season (Ofin) while the lowest value (0.35±0.25 mg/L) was recorded in wet season (Oworonsoki). The highest mean value of Surface Sea temperature was recorded in the dry season of Apapa (30.28±1.15oC) while the lowest mean value (26.41±1.15oC) was observed in Okobaba in the wet season. The chlorophyll-a concentration analyzed using standard method and MODIS satellite, in both dry and wet seasons in the sampled stations differ greatly from one another in terms of the mean concentration. The primary productivity of Lagos Lagoon was relatively low, with no significant spatial variations between sampling stations. The results of sea surface temperature, transparency and chlorophyll ‘a’ estimation from the MODIS revealed that the values were positively correlated with laboratory result with r2-value of 0.67, 0.80 and 0.77. This indicates that MODIS data and laboratory results generated for Lagos Lagoon were positively related.